Bytový dům - Procházka, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem bakalářské práce je zpracování projektové dokumentace pro provedení stavby bytového domu. Stavba je umístěna na pozemku v katastrálním území Vracov. Jedná se samostatně stojící dům o čtyřech nadzemních podlažích a jednom podzemním. Půdorysný tvar bytového domu je obdelníkový. Provozně je objekt členěn na 7 bytových jednotek o dispozicích 2+kk, 3+kk, 3+1. V podzemním podlaží jsou umístěny hromadné garáže, skladovací kóje a technické zázemí. Dům je založen na základových pásech z prostého betonu. Nosný systém je navržen jako stěnový z keramických tvarovek. V podzemním podlaží je doplněn o obvodové monolitické železobetonové stěny, průvlaky a sloup. Vodorovné nosné kostrukce se skládají z monolitických železobenových desek. Střešní konstrukce je řešena jako jednoplášťová plochá střecha. Dům je opláštěn izolačními deskami z minerální vaty.

The subject of the bachelor's thesis is the preparation of project documentation for the construction of an apartment building. The building is located on plot no. 5184/6 in the cadastral territory of Vracov. It is a detached house with four above-ground stories and one underground story. The floor plan of the apartment building is rectangular. Operationally, the building is divided into 7 residential units with layouts of 1+kk, 2+kk, and 3+1. Collective garages, storage cubicles, and technical facilities are located on the underground floor. The house is built on strip foundations made of plain concrete. The load-bearing structure is designed as a wall system made of ceramic building blocks. The load-bearing structure in the underground is supplemented with peripheral monolithic reinforced concrete walls, supporting beams, and a column. The horizontal load-bearing structures consist of monolithic reinforced concrete slabs. The roof structure is designed as a single-layer flat roof. The house is sheathed with insulation boards made of mineral cotton wool.
Apartment building
Keywords: bytový dům; jednoplášťová plochá střecha; stěnový nosný system; ETICS; Apartment building; flat single-layer roof; wall supporting structure; ETICS